Climate-driven introduction of the Black Death and successive plague reintroductions into Europe - Schmid, Boris V; Büntgen, Ulf; Easterday, W Ryan; Ginzler, Christian; Walløe, Lars; Bramanti, Barbara; Stenseth, Nils Chr (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The Black Death, originating in Asia, arrived in the Mediterranean harbors of Europe in 1347 CE, via the land and sea trade routes of the ancient Silk Road system. This epidemic marked the start of the second plague pandemic, which lasted in Europe until the early 19th century. This pandemic is generally understood as the consequence of a singular introduction of Yersinia pestis, after which the disease established itself in European rodents over four centuries. To locate these putative plague reservoirs, we studied the climate fluctuations that preceded regional plague epidemics, based on a dataset of 7,711 georeferenced historical plague outbreaks and 15 annually resolved tree-ring records from Europe and Asia. We provide evidence for repeated climate-driven reintroductions of the bacterium into European harbors from reservoirs in Asia, with a delay of 15 ± 1 y. Our analysis finds no support for the existence of permanent plague reservoirs in medieval Europe.
Keywords: climate-driven disease dynamics; History, Medieval; medieval epidemiology; epidemický výskyt choroby; lidé; Europe; Evropa; Climate; Disease Outbreaks; Yersinia pestis; podnebí; Plague; dějiny středověku; mor; Humans